Pergeseran Kategori dalam Penerjemahan Klausa Nominal Bahasa Inggris ke Bahasa Indonesia pada Novel Third Girl - Tapilatu, Terweline; Lewaherilla, August (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2024)
The translation of English noun clauses into Indonesian can result in a range of potential outcomes, some of which may be unexpected. This qualitative research focuses on the category shift variations that occur when translating English noun clauses into Indonesian and the strategies for achieving equivalence between the two texts. The data were collected from Agatha Christie's novel Third Girl and its translation